Recent advances in enzyme-based metal nanoparticles as colorimetric biosensors for the detection of pesticides: A review - Kamaruddin, Nor Khairun Bariah; Alang Ahmad, Shahrul Ainliah; Abdul Ghani, Anis (Elsevier, 2025)
Pesticides residues determination has received significant interest due to the high acute toxicity and their potential to cause long-term damage to the environment and human lives. Traditional analytical methods such as HPLC and GC-MS have been widely employed to analyse pesticides in various samples. However, these methods have drawbacks such as tedious sample preparation, complexity, expensive, and the need for highly specialized staff. As a result, there is an increasing demand for analytical methods that enable easy, quick, sensitive, selective, low-cost, and reliable detection of pesticides at trace levels. Enzyme-based biosensors offer a promising alternative, providing rapid, sensitive, and cost-effective pesticide detection. Recent advancements in colorimetric biosensors using metal nanoparticles enable on-site monitoring visible by the naked eye. These innovations may lead to portable instruments for rapid toxicity testing, revolutionizing pesticide analysis. This paper reviews insecticide types, effects, challenges, and the development of metal nanoparticle-based colorimetric biosensors for identifying pesticide.